Corporate culture, management commitment, and HRM effect on operation performance: The mediating role of just-in-time - Salma Karim; M. D. Qamruzzaman (Cogent Business & Management, 2020)
The motivation of this study is to analyze the impact of corporate culture, management commitment, and Human resources management on operational performance and the mediating effect on those relationships from JIT implemen-tation. A questionnaire-based survey was used to investigate the research ques-tions. Data from a sample of 410 manufacturing plants were analyzed using a Structural Equation Modeling (SEM) procedure. Study findings unveil direct effect running from corporate culture, management commitment, HRM, and JIT to operational performance. Considering the indirect effect i.e. the mediating role of JIT, findings suggesting that there is partial mediation available in the estimation. On the other hand, the direct effects of corporate culture, management commit-ment, and HRM on JIT is positive and statistically significant. It is advocated that the effective implementation of JIT in manufacturing units can contribute to increasing operational performance side by side the presence of other key organizational attributes.
Keywords: 650; just-in-time; operational performance; CFA; path model; SEM